The Effect of Leadership, Motivation and Organizational Culture on Employee Performance: The Case of Personal and Humar Resource Development Agency (BKPSDM) at Palembang City - Astuti, Dwi; Idris, Muhammad; Moelyati, Trisniarty Adjeng (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This research aims to investigate the impact of leadership, motivation, and organizational culture on the performance of employees at the Personnel and Human Resources Development Agency (BKPSDM) office in Palembang. This type of research is associative. The variables used by the researcher are leadership, motivation, and organizational culture on performance. The sample in this study is 86 employees of the Personnel and Human Resources Development Agency (BKPSDM) office in the city of Palembang, which was selected using Cluster Random Sampling. The data used in this study is primary data with a questionnaire data collection method. The results of this study show that (1) Leadership, motivation, and organizational culture, collectively, have a positive and significant effect on employee performance. (2) Leadership has a positive and significant impact on the company's performance.